Efeitos do carvacrol complexado em betaciclodextrina sobre a reação inflamatória de ratas submetidas à lesão por inalação de fumaça - Silva, Érika Ramos (2018)
Introduction: The high morbidity, mortality of inhaled injury victims, as well as the costs of their care, underscore the need to invest in effective and low cost treatments that contain the local and systemic pathological process. Carvacrol is a natural product with great therapeutic potential for this condition since it has antioxidant and anti-inflammatory properties. Objective: To evaluate the effect of complexed beta-cyclodextrin (β-CD) carvacrol on aerosolized rats exposed to smoke inhalation injury, considering the toxicity, antioxidant effects and histomorphological aspects of the trachea, lung and liver. Materials and methods: A randomized, longitudinal experimental study with a control group in which 24 adult rats with regular estrous cycle were divided into 4 groups: Control (without injury and without treatment), oxygen with physiological saline (GOS), oxygen with carvacrol (GOCJ) and oxygen with ultrasonic carvacrol (GOCU), with six rats per group. About 48 hours after the lung injury the rats were euthanized. The tests applied were from Shapiro-Wilk, Anova Test One Way (normal distributions), Kruskal-Wallis Test (abnormal distributions) and Dunnet's post test. The level of significance was 95% (p <0.05). Histomorphological analysis was performed in a descriptive way. Results: Variations in the hemoglobin, hematocrit, TGP / ALT, total bilirubin, creatinine and urea rates remained within the normal range. There were no differences in the MPO and TBARS levels between the groups (p> 0.05), however the levels of GSH and FRAP in the GOCJ (p <0.01 and <0.05) and COCU (p <0, 01 and p <0.01), were greater than the GOS, similar to Control. GOCU had greater preservation of tracheal epithelium, lower inflammatory response, reduction of areas of pulmonary emphysema and thickness of alveolar septa. Carvacrol has not produced any toxic cellular or hepatic effects. Conclusion: Carvacrol complexed in β-CD administered by the inhalation route, at the dose and concentration administered, presented antioxidant action, ameliorated tracheal lesions and pulmonary emphysema, without causing hepatotoxicity.